Novel Timosaponin AIII-Based Multifunctional Liposomal Delivery System for Synergistic Therapy Against Hepatocellular Carcinoma Cancer - Zhang L (Dove Medical Press, 2021)
Lijuan Zhang,1,* Shengan Zhang,2,* Min Jiang,1 Lu Lu,3 Yue Ding,3 Ninghui Ma,1 Yuan Zhao,4 Sihan Xuchen,1 Nailian Zhang1 1School of Pharmacy, Shanghai University of Traditional Chinese Medicine, Shanghai, People’s Republic of China; 2School of Basic Medicine, Shanghai University of Traditional Chinese Medicine, Shanghai, People’s Republic of China; 3Experiment Center for Teaching and Learning, Shanghai University of Traditional Chinese Medicine, Shanghai, People’s Republic of China; 4Center of Science and Technology, Shanghai University of Traditional Chinese Medicine, Shanghai, People’s Republic of China*These authors contributed equally to this workCorrespondence: Lu Lu; Yue DingExperiment Center for Teaching and Learning, Shanghai University of Traditional Chinese Medicine, Shanghai, People’s Republic of ChinaEmail yjll66@outlook.com; dingyue-2001@hotmail.comIntroduction: As high cholesterol level has been reported to be associated with cancer cell growth and cholesterol is vulnerable to oxidation, the conventional liposomes including cholesterol in the formulation seem to be challenged. Timosaponin AIII (TAIII), as a steroid saponin from Anemarrhena asphodeloides Bunge, possesses a similar structure with cholesterol and exhibits a wide range of antitumor activities, making it possible to develop a TAIII-based liposome where TAIII could potentially stabilize the phospholipid bilayer as a substitution of cholesterol and work as a chemotherapeutic drug as well. Meanwhile, TAIII could enhance the uptake of doxorubicin hydrochloride (DOX) in human hepatocellular carcinoma (HCC) cells and exhibit synergistic effect. Thus, we designed a novel thermally sensitive multifunctional liposomal system composed of TAIII and lipids to deliver DOX for enhanced HCC treatment.Methods: The synergistic effects of DOX and TAIII were explored on HCC cells and the tumor inhibition rate of TAIII-based liposomes carrying DOX was evaluated on both subcutaneous and orthotopic transplantation tumor models. TAIII-based multifunctional liposomes were characterized.Results: Synergistic HCC cytotoxicity was achieved at molar ratios of 1:1, 1:2 and 1:4 of DOX/TAIII. TAIII-based liposomes carrying a low DOX dose of 2 mg/kg exhibited significantly enhanced antitumor activity than 5 mg/kg of DOX without detected cardiotoxicity on both subcutaneous and orthotopic transplantation tumor models. TAIII-based liposomes were characterized with smaller size than cholesterol liposomes but exhibited favorable stability. Mild hyperthermia generated by laser irradiation accelerated the release of DOX and TAIII from liposomes at tumor site, and cell permeability of TAIII enhanced uptake of DOX in HCC cells.Conclusion: The innovative application of TAIII working as bilayer stabilizer and chemotherapeutic drug affords a stable multifunctional liposomal delivery system for synergistic therapy against HCC, which may be referred for the development of other types of saponins with similar property.Keywords: doxorubicin, timosaponin AIII, liposomes, hepatocellular carcinoma, cholesterol